SPIRITUAL VALUE: APA DAN BAGAIMANA - DEASY ARIYANTI RAHAYUNINGSIH (Media Bisnis, 2012)
The purpose of this article is to explain the meaning of spiritual value based on human being, workplace and accounting mechanism. This study explains the implementation of spiritual climate in people, workplace and accounting which were visibly shown in behavior, culture, actions and teamwork. Previous literature show that spiritual value appears from the people or employee, so it inspire them to influence the company’s culture and it make their lives meaningful. The main point from the article show that various socio cultural factors view spirituality as positively influencing numerous organizational outcomes.